FUNGSI KONJUNGSI KOORDINATIF DAN SUBORDINATIF BAHASA MELAYU DIALEK TELUK KUANTAN - Masnun, Masnun; Sinaga, Mangatur; Burhanudin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study examined the type and function of coordinating and subordinating conjunctions dialect of the Malay language Taluk Kuantan. This study examined to describe the type and function of conjunctions koordinatif Malay language diaelects Taluk Kuantan. The type and function of the conjunction described by type of coordinative conjunctions, types of subordinative conjunctions, conjunctions coordinative function, and the function of subordinative conjunctions based sentences Malay language diaelects Taluk Kuantan. This study examined is a qualitative research. This research data is a sentence containing conjunctions. Source of research data is a song kayat and respondents who used the dialect of the Malay language Taluk Kuantan. Data collection was tdone by using records and record (tranckript). Data where analyzed with descriptive methods. The validity of the data obtained through triangulation method. Results of this study of the type of coordinative conjunctions, types of subordinative conjunctions, conjunctions coordinative function, the function of subordinative conjunctions based sentences Malay language dialects Taluk Kuantan. Seen from the type and function, then: (1) the type of coordinative conjunctions include 18 conjunctions; (2) the type of subordinative conjunctions include 44 conjunctions; (3) conjunctions koordinative function as much as 5 to 18 conjunctions functions; (4) functions as many as 10 functions subordinative conjunctions. Coordinative conjunctions functions includes the sumfuntion, ordinal, selection, resistance, and more. Furthermore, subordinative conjunctions function includes a function of time, condition, assumptions, goals, consesive, similar , because, result, explanation, and way.Keywords: function, coordinative conjunctions, subordinative conjunctions, Malay language.2